Inside out [videorecording (Blu-Ray + DVD)] - Docter, Pete; Del Carmen, Ronnie; LeFauve, Meg; Cooley, Josh; Lin, Patrick (Cinematographer and animator) (Disney, 2019)
Growing up can be a bumpy road, and it's no exception for Riley, who is uprooted from her Midwest life when her father starts a new job in San Francisco. Like all of us, Riley is guided by her emotions ; Joy, Fear, Anger, Disgust, and Sadness. The emotions live in Headquarters, the control center inside Riley's mind, where they help advise her through everyday life.